Breast Cancer Diagnostic Imaging in Dharmais Cancer Hospital - -, KARDINAH (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43614682/Breast-Cancer-Diagnostic-Imaging-in-Dharmais-Cancer-Hospital